2020
DOI: 10.32800/abc.2020.43.0001
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect of habitat disturbance on reproduction of the critically endangered harlequin frog Atelopus varius in Las Tablas, Costa Rica

Abstract: We studied a population of Atelopus varius in Las Tablas Protected Zone in southwest Costa Rica, where we estimated occupancy rates of tadpoles along the Cotón River. In addition, we report the first tadpoles observed in the wild in 20 years. Tadpole rate of occupancy was greater in habitat containing native forest than in disturbed areas bordering cattle pasture. This same pattern was also reflected in adult hotspots, where encounter rates were higher for adults in habitat surrounded by forest versus pasture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Algunas especies como Atelopus cruciger, A. ignescens, A. varius y A. zeteki cuentan con estudios poblacionales robustos (Ron et al, 2003;Lampo et al, 2012;2017;McCaffery et al, 2015;González-Maya et al, 2018, Gómez-Hoyos et al, 2020 que han permitido estimar parámetros demográficos y evaluar tendencias poblacionales, así como identificar amenazas y su efecto sobre las poblaciones. Sin embargo, la mayoría de sapos arlequín no cuentan con estudios poblacionales de línea base y para unas pocas especies como A. elegans y A. spurrelli solo se cuenta con evaluaciones poblacionales rápidas (Gómez-Hoyos et al, 2014;Gómez-Hoyos et al, 2017) y no es posible conocer su tendencia.…”
Section: áRea De Estudiounclassified
“…Algunas especies como Atelopus cruciger, A. ignescens, A. varius y A. zeteki cuentan con estudios poblacionales robustos (Ron et al, 2003;Lampo et al, 2012;2017;McCaffery et al, 2015;González-Maya et al, 2018, Gómez-Hoyos et al, 2020 que han permitido estimar parámetros demográficos y evaluar tendencias poblacionales, así como identificar amenazas y su efecto sobre las poblaciones. Sin embargo, la mayoría de sapos arlequín no cuentan con estudios poblacionales de línea base y para unas pocas especies como A. elegans y A. spurrelli solo se cuenta con evaluaciones poblacionales rápidas (Gómez-Hoyos et al, 2014;Gómez-Hoyos et al, 2017) y no es posible conocer su tendencia.…”
Section: áRea De Estudiounclassified
“…Atelopus have suffered a particularly drastic decline; a major survey in 2005 found that, of species with sufficient population trend data (52 of 113 known species), 81% were in decline and 56% were possibly extinct. Chytridiomycosis, a disease caused by the fungal pathogen Batrachochytrium dendrobatidis, is implicated in many of the declines ( La Marca et al, 2005 ; Lampo et al, 2017 ), and habitat loss and degradation are likely also important drivers ( Gómez-Hoyos et al, 2020 ; Jorge et al, 2020b ; Santa-Cruz et al, 2017 ) . Recently, several Atelopus species thought to be extinct or locally extirpated have been rediscovered ( Barrio Amorós et al, 2020 ; Enciso-Calle et al, 2017 ; Escobedo-Galván et al, 2013 ; Tapia et al, 2017 ); however, these rediscovered populations are still at risk of extinction due to habitat loss, invasive species, low genetic diversity, and chytridiomycosis ( Byrne et al, 2020 ; González-Maya et al, 2018 ; Kardos et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%